Modeling and mapping of corporate social responsibility (CSR) - Gu, Edmund Fucheng. (2012)
CSR is the deliberate inclusion of stakeholders’ interests into corporate decision-making, which is the core business if a firm, and the honoring of a triple bottom line: people, planet and profit. Under such a theory, a corporation should possess legal, ethical and philanthropic responsibilities in addition to their primary responsibilities to maximize profit for their investors and comply with the law. CSR encourages a positive impact through its activities on the environment, consumers, employees, communities, and other various stakeholders. In this report, Carroll’s CSR pyramid concept will be used as guidance for formulation and analysis of results.